KECURANGAN PEMILU TAHUN 2024 DALAM PERSPEKTIF UU NO. 7 TAHUN 2017 DAN HADITS RIWAYAT MUSLIM - Muhamad Syamsul Maarif; Tajul Arifin (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
General elections are a fundamental democratic mechanism in maintaining state stability and electing leaders who represent the interests of the people. However, in its implementation, fraud often occurs which is detrimental to the democratic process itself. The 2024 elections in Indonesia are in the spotlight due to the emergence of various accusations of fraud committed by irresponsible parties. In this context, this journal aims to discuss fraud in the 2024 elections, with a review from the perspective of Islamic law as stated in HR. Muslims and Law no. 7 of 2017 concerning Elections. Thus, it is hoped that this journal can provide a deeper understanding of the impact and implications of election fraud on political stability and democracy in Indonesia. Through comprehensive analysis, it is hoped that this journal can contribute to efforts to prevent and overcome fraud in elections and improve the integrity of the democratic process in Indonesia. Apart from that, it is hoped that this journal can also be a reference for related parties in carrying out an honest, fair and transparent election process in order to realize a clean and trustworthy government.